7 - Book Reviews: Issa Shivji, ed., The State and the Working People Tanzania (Dakar, CODESRIA Books Series, 1986) pp. 194. / lbbo Mandaza, ed., Zimbabwe: The Political Economy of Transition (Dakar, CODESRIA Books Series, 1986) pp. 430. - Michael CHEGE (Africa Development, 1987)
abstract